Effects of feeding different postbiotics on growth performance of broilers under heat stress - Humam, A. M.; Loh, Teck Chwen; Foo, Hooi Ling; Samsudin, Anjas Asmara @ Ab Hadi; Alshelmani, Mohamed Idris; Mohamed Mustapha, Noordin (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2018)
A feeding trial was conducted to investigate the effects of different postbiotics produced by Lactobacillus plantarum on growth performance of broiler under heat stress. A total of 252 broiler chicken were allocated into 6 dietary treatments: (1) negative control (free antibiotic); (2) positive control (0.02% antibiotic of oxytetracycline); (3) 0.02% ascorbic acid; (4) 0.3% postbiotic RI11; (5) 0.3% postbiotic RS5; and (6) 0.3% postbiotic UL4. Treatments were started in finisher diet at 21 day-olds until 42 day-olds with acute heat stress (36 ± 1°C) for 3 hours per day. The results showed that birds fed postbiotic (RI11) had higher (P < 0.05) final body weight, total weight gain and best FCR compared with other treatments. However, a total feed intake (FI) were not different (P>0.05) between all the treatments. The results obtained in this study showed that feeding of 0.3% postbiotic RI11 could improve the growth performance in broilers under heat stress.